TINJAUAN HUKUM TERHADAP PERMOHONAN PEMBATALAN AKTA JUAL BELI YANG DIBUAT OLEH NOTARIS/PPAT ( STUDI KASUS PT. WAHANA WIJAYA LESTARI REALITY DENGAN YO SWIE TJIN ) - Fifian Leliana; Anis Mashdurohatun (Jurnal Akta, 2017)
Research entitled "Legal Review Against the Request of Cancellation of Deed of Sale and Purchase Between PT. Wahana Wijaya Lestari Reality With Yo Swie Tjin "aims to 1) explain and provide knowledge about the terms of making the sale and purchase deed pursuant to the prevailing rules, 2) to give understanding about judge's consideration to the request for cancellation of deed of sale and purchase between PT. Wahana Wijaya Lestari Reality with Yo Swie Tjin, and 3) provide understanding and knowledge about the legal consequences of the cancellation of the deed of sale and purchase between PT. Wahana Wijaya Lestari Reality with Yo Swie Tjin.Based on the research, it can be concluded that 1) the provision of the deed of sale and purchase based on the prevailing rules by paying attention to the important matters by fulfilling the formal and material requirements, ordering the administration, running the rules of law such as Civil Code, UUPA, UUJN, PP number 24 years 1997, PP number 37 of 1998. 2) judge's consideration of the request for cancellation of deed of sale and purchase between PT. Wahana Wijaya Lestari Reality with Yo Swie Tjin is based on the non-fulfillment of Article 1320 of the Civil Code regarding the validity of a treaty, Article 1321 of the Civil Code that there is no valid agreement if it is given by mistake, or obtained by coercion or fraud, any deviations from material requirements and formal conditions. 3) the legal consequences of the cancellation of the deed of sale and purchase between PT. Wahana Wijaya Lestari Reality with Yo Swie Tjin decided by Bandung District Court that the deed of sale and purchase number 250/2012 dated June 16, 2012 and deed of sale and purchase number 251/2012 dated June 16, 2012 made before PPAT (Plaintiff) is legal defect.Keywords: Cancellation, Deed of Sale and Purchase, Parties